Differences in desorption rate and composition of desorbed gases between undeformed and mylonitic coals in the Zhina Coalfield, Southwest China. (1st March 2019) - Chen, Yilin; Qin, Yong; Li, Zhongping; Shi, Qingmin; Wei, Chongtao; Wu, Caifang; Cao, Chunhui; Qu, Zhenghui
Abstract: Desorption is routinely employed for assessing the recoverability of coalbed gas resources. However, desorption behavior is strongly affected by coal structure. Canister desorption experiments on undeformed and mylonitic coals collected from drill holes in the Zhina Coalfield (Southwest China) were conducted to study temporal desorption rates and gas compositional shifts. Low-pressure N2 and CO2 adsorption tests revealed that the micropores, mesopores, and macropores in mylonitic coal have larger pore volumes and greater specific surface areas compared to those of undeformed coal. The "ink-bottle-shaped" pore is the main type of pore structure in mylonitic coal, whereas undeformed coal shows well-developed slit-shaped pores with good interconnectivity. The detailed desorption experiments in this study lasted 61 d and 110 h for undeformed and mylonitic coal, respectively. For undeformed coal, CH4 and C2 H6 concentrations steadily increased with desorption time, whereas N2 and CO2 concentrations progressively decreased. The gas compositional shift of mylonitic coal during the entire desorption process could be divided into two stages: an initial stage, when CH4 and C2 H6 concentrations in the desorbed gas increased (within the first 12 h), and a later stage, when they decreased rapidly; N2 and CO2 concentrations exhibited the opposite trend. The two-stage gas compositional shifts in mylonitic coal are likely linked to its pore structure. Gases in the "parallel-plate-shaped" pores of undeformed coal are mobile, whereas those in ink-bottle-shaped pores of mylonitic coal have restricted mobility. This is because CO2 and N2 can enter the narrow throats (with diameters of 3.3–3.8 Å) of ink-bottle-shaped pores, which are inaccessible to CH4 and C2 H6 because of their larger diameter, causing the late-desorbed gas of mylonitic coal to be relatively enriched in CO2 and N2 . The initial desorption rate of mylonitic coal is much greater than that of undeformed coal, which is closely related to developed microfractures in mylonitic coal. The desorption rate of undeformed coal is a power function of time, whereas that of mylonitic coal can be divided into two stages in which the relationship between desorption rate and time is a power function. The results suggest that the two-stage desorption rate is attributable to the molecular sieve effect due to the presence of massive ink-bottle-shaped pores in mylonitic coal.